An overview of the athlete`s biological passport (ABP) in professional road cycling and causes of natural variation within the ABP - Nolan, R.; Usher, R.; Heron, N. (Journal of Science and Cycling, 2019)
This article provides an overview of the athlete`s biological passport (ABP) within professional sport, with a particular focus on professional road cycling. We describe the rationale behind the ABP, what is recorded on it (particularly focusing on the haematological passport), what can cause `natural` variations to it and discuss its role within professional sport. These `natural` variations often occur at Grand Tours but more research is required into what happens during these multiple-stage road cycling races in terms of the ABP.